VEGF-B antibody and interleukin-22 fusion protein ameliorates diabetic nephropathy through inhibiting lipid accumulation and inflammatory responses - Yilan Shen; Wei Chen; Lei Han; Qi Bian; Jiajun Fan; Zhonglian Cao; Xin Jin; Tao Ding; Zongshu Xian; Zhiyong Guo; Wei Zhang; Dianwen Ju; et al. (Elsevier, 2021)
Diabetic nephropathy (DN) is considered the primary causes of end-stage renal disease (ESRD) and is related to abnormal glycolipid metabolism, hemodynamic abnormalities, oxidative stress and chronic inflammation. Antagonism of vascular endothelial growth factor B (VEGF-B) could efficiently ameliorate DN by reducing renal lipotoxicity. However, this pharmacological strategy is far from satisfactory, as it ignores numerous pathogenic factors, including anomalous reactive oxygen species (ROS) generation and inflammatory responses. We found that the upregulation of VEGF-B and downregulation of interleukin-22 (IL-22) among DN patients were significantly associated with the progression of DN. Thus, we hypothesized that a combination of a VEGF-B antibody and IL-22 could protect against DN not only by regulating glycolipid metabolism but also by reducing the accumulation of inflammation and ROS. To meet these challenges, a novel anti-VEGFB/IL22 fusion protein was developed, and its therapeutic effects on DN were further studied. We found that the anti-VEGFB/IL22 fusion protein reduced renal lipid accumulation by inhibiting the expression of fatty acid transport proteins and ameliorated inflammatory responses via the inhibition of renal oxidative stress and mitochondrial dysfunction. Moreover, the fusion protein could also improve diabetic kidney disease by increasing insulin sensitivity. Collectively, our findings indicate that the bifunctional VEGF-B antibody and IL-22 fusion protein could improve the progression of DN, which highlighted a novel therapeutic approach to DN.